Dose–Response and Temperature Dependence of the Mortality of Spider Mite and Predatory Mite Eggs Caused by Daily Nighttime Ultraviolet‐B Irradiation. (13th March 2020) - Yuan, Lifeng; Osakabe, Masahiro
Abstract: The two‐spotted spider mite, Tetranychus urticae, is an economically important agricultural pest. A novel physical control method involving daily nighttime UV‐B irradiation was recently developed for use in strawberry greenhouses. However, the overlapping of leaves after March prevents direct irradiation to T .  urticae on the lower leaf surface, decreasing control effect. Excessive UV‐B irradiation causes leaf sunscald in winter. Therefore, optimization of UV‐B irradiance and a compensatory control agent are desired. Temperature may affect the survival of organisms exposed to UV‐B, although the temperature dependence of UV‐B damage is controversial. A phytoseiid mite, Neoseiulus californicus, is a prominent predator but vulnerable to a single UV‐B irradiation. We compared dose–response and temperature dependence of UV‐B damage between T .  urticae and N .  californicus eggs under daily nighttime UV‐B irradiation. Unexpectedly, N. californicus showed greater resistance to UV‐B than T. urticae, and the mortality was increased and decreased at low and high temperatures, respectively. This makes possible the application of UV‐B doses that are lethal for spider mites but safe for phytoseiid mites. Overall, we concluded that combined use of phytoseiid mites with UV‐B lamps is advantageous to spider mite management in strawberry greenhouses. Abstract : Daily nighttime UV‐B irradiation is used for spider mite control in strawberry greenhouse in Japan. It has been known that UV‐B resistance is higher in spider mites (Tu) than phytoseiid mites (natural enemy; Nc) under a single irradiation. However, it reversed under daily nighttime irradiation, being advantageous to the combined use of phytoseiid mites with UV‐B in greenhouse. Our study also shows clear temperature dependence of the UV‐B damage to this prey–predator system; larger and smaller at lower and higher temperatures, respectively.